Survey of management in acute upper gastrointestinal haemorrhage - Thomas, G E (1980)
The answers to a questionnaire concerning attitudes of members of the British Society of Gastroenterology to the management of acute upper gastrointestinal bleeding are analysed. In the majority of cases patients were admitted to general wards under the care of physicians. Use of intensive therapy units and venous pressure monitoring varied widely. Emergency endoscopy appeared readily available and was usually the first diagnostic procedure. Double contrast radiology and emergency angiography were available in relatively few centres. Specific nonoperative treatments (angiographic and endoscopic) were scarcely employed. Most respondents agreed that elderly patients fared badly, but there was little agreement concerning other factors which influence re-bleeding or outcome. There was a wide divergence of opinion concerning the need for surgical intervention in certain hypothetical clinical situations. Despite the difficulties involved, we believe that controlled trials are necessary to improve the management of bleeding patients.